2021
DOI: 10.3389/fpsyg.2021.685856
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience Concepts Changed Teachers’ Views of Pedagogy and Students

Abstract: Advances in neuroscience reveal how individual brains change as learning occurs. Translating this neuroscience into practice has largely been unidirectional, from researchers to teachers. However, how teachers view and incorporate neuroscience ideas in their classroom practices remains relatively unexplored. Previously fourteen non-science teachers participated in a 3-week three credit graduate course focusing on foundational ideas in neuroscience. The current work was undertaken to gain insight into if and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Aside from research on surveying and dispelling neuromyths, a whole research area focuses on non-prescriptive ways to instill knowledge about the neuroscience of learning into teachers' practices. These innovative approaches, developed in the last 15 years, are mainly based on teacher professional development seminars and workshop: the "Brain Science on the Move" program (MacNabb et al, 2006), the "BrainU" summer workshops (Dubinsky, 2010;Roehrig et al, 2012;Dubinsky et al, 2013); "The Neuroscience of Learning and Memory" and other workshops (Dommett et al, 2011), "Learning and the Brain" conferences (Hook and Farah, 2013), and more recently a 36-h "Neuroscience for Educators" course (Schwartz et al, 2019;Chang et al, 2021). Rather than being trained on researcherinitiated neuroscience applications, teachers are granted agency on how to use acquired neuroscience knowledge in their practice, with the aim of promoting teacher-initiated applications: Within a constructivist setting, teachers may make personal meaning by combining the neuroscience and their own insights to the relevant contexts of their classrooms (Chang et al, 2021, p. 2).…”
Section: Are Teacher Professional Development Workhops and Seminars On The Neuroscience Of Learning Effective At Instilling Neuroscience mentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from research on surveying and dispelling neuromyths, a whole research area focuses on non-prescriptive ways to instill knowledge about the neuroscience of learning into teachers' practices. These innovative approaches, developed in the last 15 years, are mainly based on teacher professional development seminars and workshop: the "Brain Science on the Move" program (MacNabb et al, 2006), the "BrainU" summer workshops (Dubinsky, 2010;Roehrig et al, 2012;Dubinsky et al, 2013); "The Neuroscience of Learning and Memory" and other workshops (Dommett et al, 2011), "Learning and the Brain" conferences (Hook and Farah, 2013), and more recently a 36-h "Neuroscience for Educators" course (Schwartz et al, 2019;Chang et al, 2021). Rather than being trained on researcherinitiated neuroscience applications, teachers are granted agency on how to use acquired neuroscience knowledge in their practice, with the aim of promoting teacher-initiated applications: Within a constructivist setting, teachers may make personal meaning by combining the neuroscience and their own insights to the relevant contexts of their classrooms (Chang et al, 2021, p. 2).…”
Section: Are Teacher Professional Development Workhops and Seminars On The Neuroscience Of Learning Effective At Instilling Neuroscience mentioning
confidence: 99%
“…Having taken several brain-related or neuroscience courses at the undergrad level provides educators with some, but "modest" protection against neuromyths (Macdonald et al, 2017). Unlike neuroscience training at the undergrad level, training in the context of teacher professional development (workshops, seminars) looks promising (e.g., Dubinsky, 2010;Hook and Farah, 2013;Chang et al, 2021). Although effects of attending these workshops/seminars on neuromyth beliefs are unknown, positive effects on teachers' pedagogical choices have been evidenced from direct classroom behavioral observations.…”
Section: Summary Research Gaps and Future Directionsmentioning
confidence: 99%
“…Indeed, recent studies have demonstrated that neuroscience knowledge is useful for teachers, justifying its application in education (Dubinsky et al, 2013; Owens & Tanner, 2017). Teachers utilized neuroscience as a framework to guide both planned and in‐the‐moment pedagogical decisions and as a lens on student capabilities (Brick et al, 2021b; Chang, Schwartz, Hinesley, & Dubinsky, 2021; Friedman, Grobgeld, & Teichman‐Weinberg, 2019; Tan & Amiel, 2019). PD experiences around neuroscience also improve teacher competencies of self‐efficacy, motivation, self‐regulation, and self‐responsibility for student outcomes (Brick et al, 2021b), as well as positively impacting teachers' student‐centered pedagogical practices (MacNabb et al, 2006; Roehrig, Michlin, Schmitt, MacNabb, & Dubinsky, 2012; Schwartz, Hinesley, Chang, & Dubinsky, 2019).…”
Section: Figmentioning
confidence: 99%
“…Synaptic plasticity provides a justification for extending opportunities to students to reach their potentials. Embracing this idea, teachers discarded the idea of students instantly absorbing everything that was said, replacing it with a view of students who learn variably from many diverse experiences that should be provided by the teachers (Chang et al, 2021). Teachers have expressed that to learn, students must interact over multiple encounters with content, a process that takes time, requires a safe space, and develops critical thinking skills (Schwartz et al, 2019).…”
Section: How Teachers Apply Neuroscience Knowledge Of Studentsmentioning
confidence: 99%
“…Recent evidence suggests that professional developments that focus on neuroscience have the capacity to build education self-efficacy, motivation, and personal responsibility ( Brick et al, 2021b ). Chang and colleagues demonstrated that teachers who participated in a graduate-level professional development course that explored educational neuroscience concepts, shifted their focus from content and classroom management issues to their students’ needs, recognizing the importance of their students’ experiences and desire to be agents of their own learning ( Chang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%